Kualitas Kolagen Gelembung Renang Ikan Gulamah (Johnius trachycephalus) Dari Perairan Pesisir Kota Tarakan - Imra Imra; Ira Maya Abdiani; Mohammad Fadnan; Tiara Tiara; Achmad Maulana; Muhammad Rakim (Jurnal FishtecH, 2020)
Gulamah fish is a bycatch that is commonly found in the waters of the City of Tarakan. Gulamah fish in Tarakan City is processed into salted fish which produces offal waste and swimming bubbles. Swimming bubbles are known to have high collagen content. The purpose of this study was to obtain information about the length relationship between fish weight and swim bladder as well as the collagen characteristics of the gulamah swim bladder. The research was conducted in 2 stages, namely the length-weight analysis stage with swimming bubbles, and the second stage, namely the extraction and characterization of collagen from the swimming bladder of gulamah fish. The relationship between fish length and weight is a positive allometric, while the relationship between fish length and fish weight and swimming bladder of fish is a negative allometry. The physical chemical parameters of collagen obtained water content values of 29.28% - 29.30%, protein 2.86% - 2.88%, fat 9.53% - 9.55% and viscosity 11.5 ?sp.Gulamah fish is a bycatch that is commonly found in the waters of the City of Tarakan. Gulamah fish in Tarakan City is processed into salted fish which produces offal waste and swimming bubbles. Swimming bubbles are known to have high collagen content. The purpose of this study was to obtain information about the length relationship between fish weight and swim bladder as well as the collagen characteristics of the gulamah swim bladder. The research was conducted in 2 stages, namely the length-weight analysis stage with swimming bubbles, and the second stage, namely the extraction and characterization of collagen from the swimming bladder of gulamah fish. The relationship between fish length and weight is a positive allometric, while the relationship between fish length and fish weight and swimming bladder of fish is a negative allometry. The physical chemical parameters of collagen obtained water content values of 29.28% - 29.30%, protein 2.86% - 2.88%, fat 9.53% - 9.55% and viscosity 11.5 ?sp.